2017
DOI: 10.1097/qai.0000000000001327
|View full text |Cite
|
Sign up to set email alerts
|

PMTCT Service Uptake Among Adolescents and Adult Women Attending Antenatal Care in Selected Health Facilities in Zimbabwe

Abstract: Background:Age-disaggregated analyses of prevention of mother-to-child transmission (PMTCT) program data to assess the uptake of HIV services by pregnant adolescent women are limited but are critical to understanding the unique needs of this vulnerable high-risk population.Methods:We conducted a retrospective analysis of patient-level PMTCT data collected from 2011 to 2013 in 36 health facilities in 5 districts of Zimbabwe using an electronic database. We compared uptake proportions for PMTCT services between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…In Kenya, Ronen et al found that the proportion of women attending at least four ANC visits as recommended by the national guidelines was significantly lower in adolescents than adults (35.2% vs. 45.6%, P = 0.002) (Ronen et al, 2017). Similar rates of completion of four ANC visits were found among adolescents (38.9%) and adults (36.7%) by Musaradenga et al in Zimbabwe [aRR = 0.98 (0.94-1.031)] (Musarandega et al, 2017). Also, among women attending immunization clinics in South Africa, Horwood et found that a comparable number of adolescent mothers <20 years and older mothers attended ANC four times during their recent pregnancy, i.e.…”
Section: Anc Attendancesupporting
confidence: 55%
See 4 more Smart Citations
“…In Kenya, Ronen et al found that the proportion of women attending at least four ANC visits as recommended by the national guidelines was significantly lower in adolescents than adults (35.2% vs. 45.6%, P = 0.002) (Ronen et al, 2017). Similar rates of completion of four ANC visits were found among adolescents (38.9%) and adults (36.7%) by Musaradenga et al in Zimbabwe [aRR = 0.98 (0.94-1.031)] (Musarandega et al, 2017). Also, among women attending immunization clinics in South Africa, Horwood et found that a comparable number of adolescent mothers <20 years and older mothers attended ANC four times during their recent pregnancy, i.e.…”
Section: Anc Attendancesupporting
confidence: 55%
“…Also, in the cross-sectional surveys in South Africa, Ramraj et al found that in the 2010 survey, the proportion of adolescents and adults who attended ANC in the first trimester were comparable; 25.7% vs 27.0%, p = 0.38 while the proportion of adolescents attending ANC in the first trimester was lower compared to adult women in the 2011-2012 survey; 24.9% vs.30.3%, p = 0.0002 and in the 2012-2013 survey, 27.8% vs 33.7% (Ramraj et al, 2018). The findings of the five studies (Helleringer, 2017;Horwood et al, 2013;Musarandega et al, 2017;Ramraj et al, 2018;Ronen et al, 2017) that assessed the frequency of ANC visits were variable. In Kenya, Ronen et al found that the proportion of women attending at least four ANC visits as recommended by the national guidelines was significantly lower in adolescents than adults (35.2% vs. 45.6%, P = 0.002) (Ronen et al, 2017).…”
Section: Anc Attendancementioning
confidence: 86%
See 3 more Smart Citations